Ethics between Competiton and Monopoly: Text is published in periodical "Survey" 1, 2008 - Bašić, Meho (Pregled: časopis za društvena pitanja / Periodical for social issues, 2008)
The existing ethical principles have developed in differ ent parts of the world under different political, cultural, social and economic preconditions. Therefore, there is no unified set of ethical principles. As a result of these differences, legal principles that apply to ethics, social conditions and the production environment differ substantially from one country to another. At the same time, principles of global trade and competition, which are being largely adopted, bring products and services from these different cultures to the same markets. There they compete under the rules of antitrust laws and unfair competition laws. Discrimination, which can be understood as an advantage or disadvantage, depending on the point of view, is thus unavoidable. There is no short-term solution. Therefore, the price that is to be paid for globalization and universal competition is, in a way, expected and normal.